2021
DOI: 10.21307/ane-2021-006
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation effects on learning, memory and glutamate and GABAA receptor subunit gene expression in kindled rats

Abstract: Epileptic seizures are accompanied by learning and memory impairments. In this study, the effect of low frequency stimulation (LFS) on spatial learning and memory was assessed in kindled animals and followed for one month. Fully kindled rats received LFS at 4 times (immediately, 6 h, 24 h and 30 h following the final kindling stimulation). Applying LFS improved kindled animals' performance in the Barnes maze test. This LFS action was accompanied by a decrease in NR2B gene expression, an increase in the gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Our hypothesis is based on previous reports showing that abnormal, seizure-induced synaptic potentiation impairs the new synaptic potentiation and results in memory impairment. 29,44 In this regard, it has been suggested that an abnormal plasticity may occur in mPFC communications following the strong coupling of hippocampal theta and mPFC gamma bands. 52 Although there was no significant difference in coherence of delta and theta bands during post-ictal period, calculating the ratio between post-ictal and pre-ictal has shown an increase in delta and theta coherence after DBS application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our hypothesis is based on previous reports showing that abnormal, seizure-induced synaptic potentiation impairs the new synaptic potentiation and results in memory impairment. 29,44 In this regard, it has been suggested that an abnormal plasticity may occur in mPFC communications following the strong coupling of hippocampal theta and mPFC gamma bands. 52 Although there was no significant difference in coherence of delta and theta bands during post-ictal period, calculating the ratio between post-ictal and pre-ictal has shown an increase in delta and theta coherence after DBS application.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is based on previous reports showing that abnormal, seizure‐induced synaptic potentiation impairs the new synaptic potentiation and results in memory impairment. 29 , 44 In this regard, it has been suggested that an abnormal plasticity may occur in mPFC communications following the strong coupling of hippocampal theta and mPFC gamma bands. 52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations